ASSESSMENT OF RHEUMATOID ARTHRITIS ACTIVITY DURING PREGNANCY AND POSTPARTUM - E. V. Matyanova; N. M. Kosheleva; Z. S. Alekberova; E. N. Aleksandrova (Научно-практическая ревматология)
Rheumatoid arthritis (RA) is a chronic disease that may affect women of childbearing age. The occurrence  of their pregnancy is frequently accompanied by the lower activity of RA and its exacerbation may occur postpartum.  Regular disease activity monitoring  during pregnancy and postpartum  is a necessary condition  for adequate therapy correction in this category of patients.Objective: to determine an optimal method to assess RA activity during pregnancy and postpartumSubjects and methods. Thirty-two  pregnancies were prospectively followed up during each trimester and within 12 months postpartum  in 29 women with RA (according  to the 1987 ACR criteria) who had been examined at the V.A. Nasonova Research Institute  of Rheumatology  from February 2011 to August 2014.Results. Comparison  of different methods to assess RA activity demonstrated that DAS28-ESR  shows overrated estimates due to a physiological ESR elevation during pregnancy. CDAI and SDAI are greatly affected by a patient's subjective assessment of his/her  health, which may be overestimated during pregnancy and in the first month after giving birth. DAS28-CRP(3) recommended in the world literature to assess RA activity in pregnant women showed the same changes as DAS28-CRP(4). The latter  is widespread in international studies and has been validated in a large number of patients. Thus, DAS28-CRP(4) may be considered optimal to monitor RA activity during pregnancy and postpartum.